Use of Bacterial Starter Cultures in Production of Meat Products - Fatkhullaev, Abdunabi; Shaimanov, Mashrabjon; Saydullaeva, Yulduz; Abdumalikov, Islom (International Journal of Psychosocial Rehabilitation, 2020)
Obtain functional meat products in our country, various types of raw materials with increased biological activity are used, looking for ways to reduce the calorie content of products by introducing various fortifiers. In this regard, the role of plant products is difficult to overestimate. They are suppliers of vitamins, enzymes, organic acids, essential oils, pectins, dietary fiber, carbohydrates.One of the priority directions of the concept of state policy in the field of healthy nutrition of the population of the republic is the creation of technologies for the production of meat products for dietary purposes, which are easily digestible and prevent various diseases and strengthen the protective functions of the body, reducing the risk of exposure to harmful substances. A reliable way to guarantee an effective solution to this problem is the inclusion in the diet of specialized foods enriched with valuable biologically active substances to a level corresponding to the physiological needs of the human body.